Specific of Performing Breathing of the Musician Playing the Wind Instruments - Zhang Jianan (Pedagogical Discourse, 2015)
The question of forming and functioning of the correct performing breathing of the musicians, playing the music works with the help of the wind instruments instruments has been examined in the article. It is the physiological and technical foundation for realization of all other components of the music performing process. The types of music performing breathing of the musician playing the wind instruments have been cleared out, and the most optimal of them, mixed, for performing complicated artistic tasks, which offers modern composer’s creative work, has been determined.The peculiarities  of physiological processes of performing breathing in and breathing out of the musicians have been  detailed. Natural ways of mastering playing the wind music instruments with the use of the muscle support have been studied. In the article the expedient methodical complex, which assists the hole theoretic cognitive and practical development for the best music performing breathing has been offered. It is proposed to develop constantly the ability to operate personal breathing muscles and diaphragm, which appears in the process of permanent work, directed for the development of performing breathing.